Analisis Kualitas dan Pengendalian Internal Sistem Belanja Shopee Pay Later dengan Pendekatan COSO dan TAM - Yurista Amin Julyana Pratiwi; Bambang Widarno (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the quality and internal control of the Shopee PayLater digital shopping system using the Technology Acceptance Model (TAM) and the internal control framework of the Committee of Sponsoring Organizations of the Treadway Commission (COSO). As an instant financing feature on the e-commerce platform, Shopee PayLater has been widely adopted; however, limited studies have examined its efficiency and comprehensive risk control. This research employed a descriptive qualitative approach with source triangulation, thematic analysis, and narrative findings, using interviews with users and an external IT expert, internal documentation, and a questionnaire distributed to 100 respondents. The findings reveal that, functionally, Shopee PayLater fulfills the aspects of perceived usefulness and perceived ease of use in TAM. Users reported tangible benefits in terms of payment flexibility, transaction efficiency, and accessibility. Meanwhile, analysis based on the COSO framework shows that the system demonstrates relatively strong internal control, particularly in the areas of control environment, control activities, and monitoring. Nevertheless, weaknesses remain in the visibility of information and risk communication to users, which may affect trust and long-term sustainability. The study concludes that user acceptance of Shopee PayLater is shaped not only by its perceived usefulness and ease of use but also by the effectiveness of internal controls in ensuring security, transparency, and accountability